2016
DOI: 10.2152/jmi.63.227
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of proton pump inhibitor in combination with rikkunshito in patients complaining of globus pharyngeus

Abstract: The present findings suggest the existence of a high prevalence of LPRD in patients complaining of GP. The data also suggest that gastroesophageal dysmotility is involved in GP, in addition to excessive acid reflux. The pre-therapeutic laryngopharyngeal symptoms and endoscopic findings could not predict the efficacy of the treatment for GP. J. Med. Invest. 63: 227-229, August, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…39 Two studies of RKT looked at its efficacy in PPI-refractory LPR symptoms. Nakano et al 27 treated 22 PPI non-responders with globus with PPI+RKT, 14 experienced significant improvement in globus symptoms (>50% improvement measured by a VAS). Tokashiki et al 28 treated patients with persistent LPR symptoms despite 2 weeks of PPI therapy with RKT alone or RKT+PPI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Two studies of RKT looked at its efficacy in PPI-refractory LPR symptoms. Nakano et al 27 treated 22 PPI non-responders with globus with PPI+RKT, 14 experienced significant improvement in globus symptoms (>50% improvement measured by a VAS). Tokashiki et al 28 treated patients with persistent LPR symptoms despite 2 weeks of PPI therapy with RKT alone or RKT+PPI.…”
Section: Resultsmentioning
confidence: 99%
“…Although RKT alone improved globus, PPI treatment was discontinued immediately prior to the study and may have confounded the result. Similarly, it is unclear if the improvement with RKT in the study of Nakano et al 27 is because of an increased duration of PPI treatment or the addition of RKT since there was no control group. Previous studies have found a duration of 3 months is needed for a PPI response, which is longer than the time period used in either study.…”
Section: Discussionmentioning
confidence: 98%
“…In addition to behavioral approaches, certain non‐pharmacological supplements have been utilized in managing globus symptoms. Rikkunshito, a Japanese herbal medication, has been reported to improve globus symptoms, when used alone or combined with PPIs in patients with concurrent reflux disease 65,66 . In a single case report, acupuncture is reported to benefit globus symptoms 67…”
Section: Management Of Globusmentioning
confidence: 99%